(untitled) (Research, Society and Development, 2025)
Introduction: Leptospirosis is a global bacterial zoonosis caused by Leptospira. Although traditionally rural, it has reemerged in urban areas due to poor sanitation, presenting in forms ranging from mild to the lethal Weil’s syndrome, which requires high clinical suspicion. Objective: The purpose of this report is to describe the clinical case of an urban adolescent with icteric leptospirosis complicated by Weil’s syndrome and reactive cholecystitis, emphasizing the clinical, biochemical and imaging findings that guided the differential diagnosis, as well as the favorable therapeutic evolution after the establishment of early antibiotic management. Methodology: A retrospective single-case study was conducted following CARE guidelines. Clinical, laboratory, and imaging data were analyzed from the electronic medical record of a pediatric patient, with informed consent obtained from the parents. Case Presentation: A 14-year-old urban male from Colombia, without rural exposure, presented with fever, headache, and an unusual pruritic rash, progressing to marked jaundice and abdominal pain. Labs showed thrombocytopenia, direct hyperbilirubinemia (4.0 mg/dL), and elevated CPK, ruling out dengue . Positive IgM confirmed leptospirosis, and ultrasound revealed reactive acalculous cholecystitis. After treatment with ceftriaxone and doxycycline, the patient fully recovered and was discharged on the third day. Discussion: This case illustrates the diagnostic complexity of urban leptospirosis, highlighting atypical manifestations such as rash and cholecystitis. Rapid differentiation from other febrile illnesses and antibiotic use prevented major complications. Conclusion: It is vital to include leptospirosis in the differential diagnosis of urban febrile icteric syndromes. Active surveillance and timely antibiotic treatment are decisive in reducing lethality, reinforcing the need for a preventive One Health approach.